Use of digital media and its impact on generation Y & Z - Ordoñez Guartazaca, Marjorie (Revista Universidad de Guayaquil, 2019)
The present research raises what is the behavior of certain Y & Z generations in the use of digital media, and how this influences the new generations through close interaction with the students of the University of Guayaquil of the Faculty of Administrative Sciences, in order to analyze their behavior when using digital media. The quantitative methodology was used to gather information through the surveys. The main results show the incidence of the use of digital media in both generations and its importance in the development of the interconnected digital society.